Development of a material characterization method for the Medieval codices of the collection from the Monastery of Alcobaça - Tourais, Ana Sofia Santo (2021)
The collection of codices from the Monastery of Alcobaça is one of the most relevant in Europe because it contains one of the largest sets of codices that preserve Medieval materials. In this sense, it is an important primary source of information for a complete study on an entire community. In this dissertation we aimed at studying this collection’s materiality. To do that, we designed a characterization method following leading tendencies recommend by main scholars in the field. The method was constructed as a structured record, done in a table-based digital format with a controlled vocabulary which was compiled in a multilingual glossary. It allows to perform a detailed codicological analysis of the codices’ physical features and to record pioneering results achieved with advanced analysis on surviving materials. Thus, it provides researchers with codicological and analytical information on each codex and on the entire collection. Results attained revealed that the method allows researchers to perform interpretative analyses of recorded data and to compare it between itself and with related bookbinding literature. In the case of this dissertation, based on a comparative codicological analyses we were able to propose a chronology for different binding elements of three selected codices: Alc. 341, Alc. 413 and Alc. 414. This chronology and our observations also support the theory that these codices’ current binding was done in this order. Their material analyses allowed a general identification of inks, paints and sewing threads’ fibres, and a more concrete identification of wood and metallic materials. Paints and metallic materials’ identification generally match literatures’ findings, but wood analyses revealed completely new results with the potential detection of Fagus (a genus that was not considered in previous works regarding this collection). It also became evident that skin-based material analyses’ methodologies, must be further developed for more positive results.